BULLYING AND MEASURES TO REDUCE IT: PERCEPTION OF HIGH SCHOOL STUDENTS IN DIFFERENT EDUCATIONAL CONTEXTS - Salmazo, Alicia Helena Mendes (2021)
Bullying is a systematic aggressive act, involving threat, intimidation or coercion, practiced against someone, by an individual or a group of people. It is a problem still present in young people, especially in the school environment. The objective of this work was to analyze the reasons of bullying victimization  and measures to minimize them, in different educational contexts, perceived by students. A questionnaire was used, adapted from the “Peer Victimization Scale” model by Mynard and Joseph (2000), with two questions about the occurrence of victimization by bulliyng and measures to minimize it. Student responses were categorized for each question. The responses in category 1 were classified as: my fault, the fault of the other and naturalization. Category 2 responses were classified as: Individualized assistance, awareness, punishment, supervision and nothing to do. The categorized results were related to quantitative victimization data and considerations were made for anti-bullying actions in schools based on the results.